Eye lens dose of medical personnel involved in fluoroscopy and interventional procedures at a Malaysian Hospital - Wong, Jeannie Hsiu Ding; Anem, Lydia Esther Andrew; Tan, Suzet; Tan, Sock Keow; Ng, Kwan Hoong (Elsevier, 2019)
Objective: This study measured the radiation exposure of the eye lens of medical personnel performing fluoroscopy and interventional procedures at the Sarawak General Hospital in Kuching, Sarawak, Malaysia. This study was the first in Malaysia to utilise in vivo radiation measurement relatively near the eye lens. Methods: 41 medical personnel performing 79 procedures were monitored for their eye lens exposure using the NanoDot™ optically-stimulated luminescence dosimeters (OSLD) taped to the outer canthus of their eyes. The air-kerma area product (KAP), fluoroscopy time (FT) and number of procedure runs were also recorded. Results: KAP, FT and number of runs were strongly correlated. However, only weak to moderate correlations were observed between these parameters with the measured eye lens doses. The average median equivalent eye lens dose was 0.052 mSv (ranging from 0.0155 to 0.672 mSv). The eye lens doses of primary operators were found to be significantly higher than their assistants due to the closer proximity to the patient and X-ray tube. The left eye lens of the operators received the highest amount of radiation due to their habitual positioning towards the radiation source. Conclusion: KAP and FT were not useful in predicting the equivalent eye lens dose exposure in interventional radiological procedures. Direct in vivo measurements were needed to provide a better estimate of the eye lens doses received by medical personnel during these procedures. This study highlights the importance of using direct measurement, such as OSLDs, instead of just indirect factors to monitor dose in the eye lens in radiological procedures. © 2019 Associazione Italiana di Fisica Medica